Complete and incomplete Kawasaki disease: Clinical differences and coronary artery outcome from a national prospective surveillance study in Switzerland - Bressieux-Degueldre, S.; Gradoux, E.; Di Bernardo, S.; Sekarski, N. (Frontiers in Pediatrics, 2023)
This national prospective surveillance study aimed to compare clinical presentation, laboratory, treatment and coronary artery outcome in patients with incomplete and complete Kawasaki disease (KD). From March 2013 to February 2019 children with a diagnosis of complete and incomplete KD were reported by the Swiss Paediatric Surveillance Unit and prospectively enrolled. Clinical data, laboratory values, treatment and echocardiographic features were collected at diagnosis and at one year of follow up. Data were compared between children with complete and incomplete KD. 351 questionnaires were registered from children with a diagnosis of KD. 219 (62.4%) children had complete KD and 132 (37.6%) children had incomplete KD. Children with incomplete KD were younger in age and did have longer duration of fever, however, there were no differences in C-reactive protein levels. All but 4 children received intravenous immunoglobulins treatment, whereas 14% of children were treated with corticosteroids. Children with incomplete KD were more often treated with corticosteroids than children with incomplete KD (p-value 0.01). At diagnosis 39 (11.1%) patients had coronary artery dilation only and 57 (16.2%) had at least one coronary artery aneurysm. There were no differences in coronary artery involvement between both groups. At follow up, 273 of 294 patients (92.8%) had no coronary artery involvement with no difference between the two groups (p=0.609). The overall incidence of coronary artery aneurysm at diagnosis was 16.2%. At follow up most coronary artery aneurysms had regressed, and coronary artery aneurysms was present in only 5.8% of the patients. Coronary artery aneurysms were slightly more frequent in patients with incomplete KD at follow up (p-value (0.039) but not at diagnosis (p-value 0.208). Although clinical presentation in children with incomplete and complete KD are different, freedom from coronary artery involvement did not differ. The use of corticosteroids appears to be protective against development of coronary artery aneurysms in these patients. However, the results of this study suggest a lower rate of coronary artery aneurysms regression in patients with incomplete KD. Further studies on a larger scale are needed to assess the risk of non-regression of coronary artery aneurysms in this particular patient group.